Aspekty dydaktyczne internetu rzeczy - Szabłowski, Stanisław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
W opracowaniu wyjaśniono podstawowe pojęcia niezbędne do zrozumienia problematyki IoT w edukacji inżynierskiej i informatycznej. Przeprowadzono analizę możliwości nauczania zagadnień Internetu rzeczy na bazie dostępnych aplikacji ThingSpeak i Cisco PacketTracer oraz wskazano ich walory edukacyjne. Przyjęto modelowanie i projektowanie jako wiodące metody uczenia się zagadnień IoT. Opisano domową stację pogodową jako przykład dydaktycznego projektu IoT.

The study explains the basic concepts necessary to understand the issues of IoT in engineering and IT education. Ananalysis of the possibilities of teaching the issues of the Internet of Things was carried out on the basis of the available ThingSpeak and Cisco PacketTracer applications and their educational values were in dicated. Modeling and design have been adopted as the leading methods for learning IoT topics. A home weather station is described as an example of a didactic IoT project.
Didactics aspects of the Internet of Things
Keywords: Internet rzeczy; platforma ThingSpeak; Cisco PacketTracer; nauczanie IoT; Internet of Things; ThingSpeak platform; IoT teaching